Improving Precision in Navigating Laparoscopic Surgery Instruments toward a Planar Target Using Haptic and Visual Feedback - Howard, Thomas; Szewczyk, Jérôme (Frontiers in Robotics and AI, 2016)
The poor ergonomics of laparoscopic surgery is a widely recognized source of difficulty for surgeons, leading to sub-optimal performance on their part and sometimes injury to the patient. The main recognized causes for such degraded performance are lost and distorted perception of interaction forces and degraded instrument navigation capabilities. The latter, due mainly to losses in visual and kinesthetic depth perception and modified hand-eye coordination, can prevent precise navigation of instruments toward surgical targets or away from sensitive anatomic structures. This situation prompts us to explore novel methods for efficiently assisting the surgeon during intra-corporeal instrument navigation. Here, we present a series of experiments aimed at providing insights into the effectiveness of haptic (tactile and kinesthetic), visual, and combined feedback in assisting the navigation of a laparoscopic instrument tip toward a surgical target. We placed subjects in front of a laparoscopic trainer and tasked them with following various instrument tip trajectories within a target plane while minimizing both deviation from said target and task execution time. Feedback on the level of deviation was provided alternately through visual on-screen cues (in the form of a bar-graph), tactile cues provided by vibration motors (off the shelf DC eccentric rotating mass motors) placed in the subjects hand, and/or kinesthetic cues provided by a haptic interface (6 degrees-of-freedom Haption Virtuose 6D interface) co-manipulating the surgical instrument. Evaluations of these forms of feedback over two series of experiments involving a total of 35 subjects (34 non-surgeon novices, 1 surgeon intern with experience in laparoscopy) show positive impacts of providing such feedback on precision in instrument navigation, and provide insights into possibilities for implementation in surgical assistance systems. Visual, tactile, and combined cues lead to increased precision in navigation (up to 25% increase in time on target, and 32% reduction in deviation amplitudes), but usually at the cost of reduced task execution speed (mean task execution times almost doubled under provision of visual feedback). However, the use of kinesthetic feedback through soft virtual fixtures provided in a co-manipulated robot-assisted surgery set-up both significantly improved precision (32% increase in time on target, and 70% reduction in deviation amplitudes) and task execution speed (30% reduction in task completion times). Although tactile feedback yielded slightly better performance than visual feedback in terms of overall precision, the addition of visual feedback was shown to be helpful in correcting larger deviations from the target. These preliminary results are promising for implementation of low-cost tactile or combined visual and tactile feedback in applications to conventional laparoscopic instrument navigation, as well as to robot-assisted laparoscopic surgery. Furthermore, subjective evaluation showed that all feedback was generally perceived as intuitive and helpful, although surprisingly, it did not improve the subjects capability to assess their own performance. Finally, the patterns of improvement in precision when navigating toward targets observed in novice subjects hold true in experiments with a surgeon intern, with the added benefit of no visible degradation of performance in terms of task execution speeds when compared to performance without feedback. Overall, these results indicate a positive impact of haptic and visual feedback on the speed/accuracy trade-off performed by surgeons when navigating toward targets, with a beneficial impact of experience in laparoscopy on the capability to effectively use the provided feedback.